CASI Method for Improving the Usability of IDS - Mazlina, Abdul Majid; Butt, Saad Masood; Suziyanti, Marjudi; Butt, Shahid Masood; Azura, Onn; Butt, Moaz Masood (Publications International, 2015)
Usability evaluation methods have gained a sbstantial attention in networks particularly in Intrusion Detection System (IDS) as these evaluation methods are envisioned to achieve usability and define usability defects for a large number of practical software’s. Despite a good number of available survey and methods on usability evaluation, we feel that there is a gap in existing literature in terms of usability evaluation methods, IDS interfaces and following usability guidelines in IDS development. This paper reviews the state of the art for improving usability of networks that illustrates the issues and challenges in the context of design matters. Further, we propose the taxonomy of key issues in evaluation methods and usability problems. We also define design heuristics for IDS users and interfaces that improves detection of usability defects and interface usability compared to conventional evaluation heuristics. The similarities and differences of usability evaluation methods and usability problems are summarized on the basis of usability factors, current evaluation methods and interfaces loopholes.